Implementing the agroecological transition: weak or strong modernization of agriculture? Focus on the mycorrhiza supply chain in France - Valérie Angeon; Rebecca Bilon; Marie Chave (European Regional Science Association (ERSA), 2014)
Industrial agriculture and its technological package (intensive farming, mechanization, use of chemicals) are no longer in position to ensure food security (Altieri et al., 2012). To overcome the strongly negative externalities produced by this model, agroecological transition may be considered as a privileged pathway. Nevertheless, two major evolutions of modern agriculture can be distinguished (Duru et al., 2014): the weak (implementation of "good practices" that intend to improve the efficiency of chemicals and/or reduce their use) versus strong (substitution of chemical inputs by biodiversity providing ecosystem services) ecologization of agriculture. In this article, we focus on the enhancement of mycorrhiza (symbiosis between roots and soil fungi), key elements of biodiversity becoming a momentum in matter of agroecological engineering. We study the complex interrelationship structure implying a diversity of actors that are closely linked, share norms of action, values. The result of their coordination (market and non-market) and the networks within these actors interact shape a "socio-technical regime" (Geels and Shot, 2007; Vanloqueren and Baret, 2009). This concept is close to Dosi's (1982) evolutionary approach of industrial processes and changes that are embedded in the systems of innovation approach. The aim of this article is to appraise the robustness of the socio-technical regime grounded on the use of mycorrhiza. We pay attention to the most widespread technology: the inoculation of industrial strains. We base our analysis on the identification of the set of actors who pilot the technological trajectory of this agroecological pattern (industrials, scientists, public authorities, farmers). We then produce a heuristic map. Using the stakeholder analysis (Mitchell et al., 1997), we conduct around 30 interviews that permit (i) to characterize the nature of the relationships among agents (information sharing, subsidies, goods and services) and (ii) to specify in what extent these interactions stabilize the existing technological paradigm. We show that the agroecological pattern based on the inoculation of industrial strains corresponds to a weak form of ecologization of agriculture and hinders the emergence of alternative innovative niches (i.e. mobilization of indigenous mycorrhizal networks) that could support a strong modernization of agriculture. Our results then demonstrate that the prevailing socio-technical regime is deeply reinforced although changes occur in the production process.
Keywords: B52; O33; Q01; Q55; 330; systems of innovation; evolutionary economics; socio-technical regime; technological paradigm; agroecological transition code: